Warhol selon Avedon : le paradoxe en héritage ? - Véronique Béghain (Transatlantica)
This paper links the iconographic tradition related to Saint Sebastian with Valerie Solanas’s « performance » as two visible legacies included in Warhol’s body as photographed by Avedon in his 1969 portrait entitled « Andy Warhol, Artist, New York City, 8/20/69 », in many ways a paradoxical portrait with an undecidable meaning arising from the tension between surface and depth, reflection and construction, clinical approach and staging.